2019
DOI: 10.26434/chemrxiv.7905344.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmon-Induced Hot-Carrier Generation differences in Gold and Silver Nanoclusters

Abstract: In the last thirty years, the study of plasmonic properties of noble metal nanostructures has become a very dynamic research area. The design and manipulation of matter in the nanometric scale demand a deep understanding of the underlying physico-chemical processes that operate in this size regimen. Here, a fully atomistic study of the spectroscopic and photodynamic properties of different icosahedral silver and gold nanoclusters have been carried out by using Time-Dependent Density Functional Tight-Binding (T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…As the Coulomb energy contribution is carried mainly by nonresonant transitions ( Supplementary Figure S6 ), the occupation probabilities of the electron and hole states contributing to these nonresonant transitions oscillate analogously to the Coulomb energy. The oscillations are especially visible in the occupations of electron and hole states that form the plasmon, 35 that is, the states near the Fermi energy, often referred to as Drude carriers. 49 The oscillatory population and depopulation of these states indicate that they would not likely be individually separable while they are a part of the plasmon as the Coulomb interaction is an essential part of the excitation itself.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Coulomb energy contribution is carried mainly by nonresonant transitions ( Supplementary Figure S6 ), the occupation probabilities of the electron and hole states contributing to these nonresonant transitions oscillate analogously to the Coulomb energy. The oscillations are especially visible in the occupations of electron and hole states that form the plasmon, 35 that is, the states near the Fermi energy, often referred to as Drude carriers. 49 The oscillatory population and depopulation of these states indicate that they would not likely be individually separable while they are a part of the plasmon as the Coulomb interaction is an essential part of the excitation itself.…”
Section: Resultsmentioning
confidence: 99%
“… 4 , 5 , 20 26 Whereas atomic-scale effects in nanoplasmonics, in general, have been increasingly addressed in recent years, 27 32 atomic-scale modeling of plasmonic HC generation is only emerging. 33 35 In particular, detailed atomic-scale distributions of plasmon-generated HCs, to our knowledge, have not yet been scrutinized. In the context of photocatalysis detailed understanding of plasmonic HC generation at the atomic scale is, however, of paramount importance as chemical reactions take place at this size scale.…”
mentioning
confidence: 99%
“…Single layer hBN is also known as white graphene. It has been well demonstrated that the silver substrate could provide a much narrower width of the resonance curves and also deeper resonance dips [ 49 , 50 ]. Two-dimensional perovskite is sandwiched between the hBN and graphene layers, where its optical property will not be affected due to oxidization and liquid contaminations [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of DFTB promises significant computational cost savings and therefore ability to treat larger systems also with the real-time time-dependent approaches. RT TD-DFTB has been gaining use in plasmonics [87,88,176,177]. In RT TD-DFTB, the Liouville-von Neumann equation…”
Section: Real-time Td-dftbmentioning
confidence: 99%
“…While some more well-known approaches such as classical and TD-DFT were previously reviewed [82][83][84], the bulk of DFT-based literature deals with system sizes limited to a few nm, which is on the lower part of the range of particle sizes used in PV. We therefore specifically highlight emerging approaches which have the potential to significantly enhance modeling capabilities in the coming years, in particular, by allowing modeling at realistic length scales (of particles beyond 10 nm which are of most interest to plasmonic solar cells but remain problematic with Kohn-Sham DFT), such as timedependent orbital-free DFT [85,86], linear response and real-time time-dependent density functional tight binding [87][88][89][90] and machine learning-based approaches, and by allowing modeling beyond the single-particle based (DFT) picture with many-body perturbation theory [78][79][80][81]. The latter approach, while being computationally expensive, is also finding increasing use in the modeling of plasmonics as access to computing power expands, and is therefore explicitly included in this review.…”
Section: Introductionmentioning
confidence: 99%